Sharia Literacy and Social Dimension of Indonesian Education: A Study of Financial Inclusion in Islamic Boarding Schools Through Digital Transformation - Alhassan, Muneera Fawaz H.; Rahayu, Elinsyi; Hidayat, Dita Nafira; J, Salwa; Nurhasanah, Nurhasanah (Graduate School of UIN Syarif Hidayatullah Jakarta, 2024)
This research explores strategies for enhancing Sharia financial literacy and inclusion in Islamic boarding schools through digital transformation. It highlights the potential of digital technology to improve students' understanding and practice of Sharia finance. The study examines the influence of cultural and social factors on the adoption of digital technology and the importance of adhering to Sharia principles in digital financial transactions. Using sociological frameworks such as Rogers' Diffusion of Innovations, Bourdieu's Habitus and Capital, and Weber's Social Action Theory, the research demonstrates that digital tools like e-learning platforms and Sharia financial apps effectively boost financial literacy. Collaboration with Sharia financial institutions further promotes financial inclusion. This study provides valuable insights for developing Sharia financial literacy programs and informs policy development.